A Reluctant Opposition: Soviet Liberals within the Moscow Tribune. Issue 3 (2022) - Sauvé, Guillaume
Abstract : The Moscow Tribune was the most prestigious and influential political discussion club in recent Russian history. In the last years of the Soviet Union, the club regularly gathered Moscow's who's who of the Soviet liberal intelligentsia and played a prominent role in the rise of movements that challenged Gorbachev's leadership over reforms. This article tells the forgotten story of the Moscow Tribune to historicize the notion of opposition in the context of perestroika, drawing on comparative studies of dissent in late communist regimes. A close analysis of the debates taking place at the club between 1988 and 1991 shows that Soviet liberals' dramatic shift towards opposition was reluctant, reactive, and constantly disputed, thus revealing a lasting yet implicit dilemma regarding the need for opposition in democracy.